Prone Position Ventilation Used during a Transfer as a Bridge to Ecmo Therapy in Hantavirus-Induced Severe Cardiopulmonary Syndrome. (15th July 2013) - Cornejo, R.; Ugalde, D.; Llanos, O.; Bisbal, P.; De la Barrera, L.; Romero, C.; Neira, R.; González, Roberto; Gajardo, J.
Abstract : Background . Transport of critically ill patients is a complex issue. We present a case using prone positioning as a bridge to extracorporeal membrane oxygenation (ECMO), performed by a critical retrieval team from a university hospital. Case Report . A 28-year-old male developed fever, progressive respiratory failure, and shock. He was admitted to ICU from a public hospital, and mechanical ventilation was begun, but clinical response was not adequate. ECMO was deemed necessary due to severe respiratory failure and severe shock. A critical retrieval team of our center was assembled to attempt transfer. Prone positioning was employed to stabilize and transfer the patient, after risk-benefit assessment. Once in our hospital, ECMO was useful to resolve shock and pulmonary edema secondary to Hantavirus cardiopulmonary syndrome. Finally, he was discharged with normal functioning. Conclusion . This case exemplifies the relevance of a retrieval team and bridge therapy. Prone positioning improves oxygenation and is safe to perform as transport if performed by a trained team as in this case. Preparation and organization is necessary to improve outcomes, using teams and organized networks. Catastrophic respiratory failure and shock should not be contraindications to transferring patients, but it must be done with an experienced team.